Student Satisfaction After Attending Individual Counseling Services in terms of Gender and Counselor's Working Period - Kenny Dwi Fhadila; Afdal Afdal (Jurnal Neo Konseling, 2020)
This research was motivated by the existence of several students who had problems and attended individual counseling services and then did not come back for further counseling. This can be seen because students feel less satisfied after getting individual counseling services because students do not get new knowledge, do not get new solutions and students feel that the counseling teacher does not understand student expectations. The purpose of this study was to describe student satisfaction after participating in individual counseling services in terms of gender and work tenure of the counseling counselor / counselor. This study used a comparative descriptive approach with a 2x2x2 factorial model. This research was conducted on class XI and XII students of SMA N 8 and  SMA N 13 Padang in the 2020/2021 school year. The sample size is 90 students with purposive sampling technique. The research instrument was a student satisfaction questionnaire after participating in an office counseling service using the Guttman scale mosel. Data were analyzed using analysis of variance techniques (ANOVA). There is no interaction of student satisfaction after participating in individual counseling services seen from the gender of the student, the gender of the counselor and the working period of the counselor / counselor simultaneously.